Evaluation of dyslipidemia based on ATP III guideline in adults in Southwest Iran: a population-based study - Bahman Cheraghian; Nader Saki; Sara Sarvandian; Seyed Jalal Hashemi; Seyed Ahmad Hosseini; Sara Saki; Zahra Rahimi (Scientific Reports)
Abstract Dyslipidemia is a primary risk factor for cardiovascular disease. This study aims to investigate the prevalence of dyslipidemia and its associated risk factors in the southwest region of Iran. This population-based cross-sectional study was conducted with 9846 participants aged 35 to 70 in southwest Iran. Data was collected on socioeconomic factors, demographic characteristics, comorbidities, laboratory tests, anthropometric measurements, and lifestyle variables. The criteria for dyslipidemia were based on the ATP III classification. A multivariable logistic regression model was used to control for potential confounders. Results showed that the overall prevalence of dyslipidemia was 43.5%, with abnormal levels of HDL, LDL, TC, and TG at 17.9, 21.8, 36.2, and 44%, respectively. The multivariable logistic regression analysis revealed that males (OR 1.92, 95% CI 1.74−2.14), individuals with abnormal waist circumference (OR 1.88, 95% CI 1.67−2.12), those with low physical activity (OR 1.30, 95% CI 1.15−1.46), smokers (OR 1.17, 95% CI 1.05−1.31), rich people (OR 1.19, 95% CI 1.04−1.36), and patients with hypertension (OR 1.16, 95% CI 1.05−1.27) had higher odds of dyslipidemia. Our findings suggest that dyslipidemia is a complex condition that is influenced by various biological and lifestyle factors. Different prevention and treatment strategies may be necessary for various population subgroups.